Big Bird in Japan - Children's Television Workshop ([United States] : Sony Music ; New York, NY : Distributed by Sony Wonder, 2004)
The excitement begins when Big Bird and Barkley the Dog are separated from their tour group while on a trip to Japan. They meet a mysterious Japanese woman who shows them the beauty of Japan and the Japanese people.
Originally produced for television in 1991.
At head of title: Sesame Street.
Executive producer/director/writer, Jon Stone ; art director, Alan Compton ; music, Stephen Lawrence, Joe Raposo, Peter Schickele ; costume designer, Ramsey Mostoller.
DVD, region 1, full screen presentation; Dolby Digital.
In English or Japanese dialogue.
Closed-captioned.
Keywords: Big Bird (Fictitious character) -- Juvenile films; Japan -- Description and travel -- Juvenile films; Television programs for children; Films for the hearing impaired